Selected aspects of the university social responsibility (USR) in Poland - Korkosz-Gębska, Jolanta (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: In accordance with the Law on Higher Education, the mission of the Polish education and science system is to provide top quality education and scientific activity, develop civic attitudes, and be involved in social development and creation of an innovation-based economy. The third mission of an academy focusing on social responsibility is to build mutual relations with the community in order to popularise and implement research results. In recent years, university social responsibility (USR) has turned into one of the priorities for Polish academic authorities, although research shows this to be a new matter in this area, which often leads to incorrect classification of activities resulting from regular obedience of the law as activities confirming the social responsibility of the organisation. Aim: The main objective of this article is to identify examples of socially responsible activity assumed by Polish academies and demonstrate the similarities with such activities conducted by other foreign academies. The author also wanted to associate the name of Professor Karol Adamiecki with social responsibility affairs what is usually overlooked in studies on this subject. Results: The conducted analyses confirmed that Polish academies are assuming socially responsible activity voluntarily and not just in order to fulfil the criterion of conformity with the currently effective laws. Furthermore, these results also confirm that — in comparison with academies abroad — the involvement of Polish academies in implementation of the concept of social responsibility is on the right path of development, although not as popularised, which only confirms the genuine and non-marketing approach to the matter of social responsibility.